Interpretasi Angklung dalam Bentuk Visual pada Pertunjukan Video Mapping - Rio Julian Akbar (PANTUN, 2018)
The paper aims to analyze several works produced by “Sembilan Matahari” in applying visual elements of Angklung represented on video mapping in the certain performance either in domestic or foreign countries. The study is conducted trough preliminary, literature, and the analysis of the works performed. The data obtained are analyzed by using Richard E. Palmer’s hermeneutic. The study tries to interpret and signify the signs in the video mapping performance. The result shows that video mapping is one of new media arts which has its own atractiveness to the audience. It is quite potential as alternatif media for promoting the culture heritage in each of the works produced.Keywords: Angklung, Interpretasi, Video mapping